AN ANALYTICAL STUDY ON THE FINANCIAL PERFORMANCE OF LEADING HFC OF INDIA - Mehta, Pritesh Prabhulal; Raval, Navjyot (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper embarks on an analytical journey to scrutinize financial performance of leading Housing Finance Companies (HFCs) in India, entities pivotal to the nation’s economic fabric due to their crucial role in fulfilling housing finance needs. Given the significant contribution of these institutions to the housing sector and, by extension, to the overall economic development, understanding their financial health becomes imperative. Through a meticulous examination of various financial performance indicators over a defined period, this study aims to shed light on the operational efficiency, profitability, liquidity, and solvency of these pivotal institutions. Adopting a structured methodology, the paper selects prominent HFCs based on specific criteria, leveraging public financial data and employing an array of analytical tools for an in-depth analysis. With an industry overview setting the context by delineating the current market landscape, regulatory environment, and competitive dynamics, the study progresses to a detailed financial performance analysis. Here, a comparative approach is adopted, benchmarking selected HFCs against industry averages and each other, using a suite of financial ratios that encapsulate profitability, liquidity, solvency, and operational efficiency.